One-dimensional Polymeric Nanocomposites in Drug Delivery Systems - Ashique, Sumel; Upadhyay, Aakash; Gulati, Monica; Singh, Dilpreet; Chawla, Pooja A.; Chawla, Viney (Current Nanoscience, 2023)
Nanocomposites have become a promising approach for drug delivery in the pharmaceutical field due to several benefits and current research development. Polymer nanocomposites (PNCs) are blends of nanomaterials and polymers with at least one-dimensional structure and one component in the sub-100 nm range. By incorporating nanoparticles into the polymer matrix, it is feasible to create a new class of given characteristics. Nano-clay (a type of nanocomposite) is mainly used for the controlled release of therapeutics in various disease conditions. Nanocomposites are promising drug delivery systems due to several advantages, including surface and rheological characteristics. Considering physical and chemical properties, nanocomposites are divided into two different components. Polymer-fabricated nanocomposites are potentially used in multi-particulate systems, which results in a controlled drug release profile with improved mechanical integrity. Nanotechnology-based drug delivery nanocomposites offer an improved half-life, greater biocompatibility, minimum immunogenicity, site-specific targeting, and avoid membrane barriers. Specifically, one-dimensional (1D) nanocomposites show promising responses in theranostics due to improved surface area-to-volume ratios that offer specific targeting, improved encapsulation efficiency, and susceptibility to biomolecules.
Keywords: properties of nanocomposites